Connected Stability Analysis of Delay Systems via the Matrix-Valued Lyapunov Function - Sun, J.F.; Wang, X.L. (Прикладная механика, 2013)
By the method of combining the matrix-valued Lyapunov functional and comparison theorem, connected Lyapunov stability and practical stability of large scale delay system are studied deeply. A series of new sufficient conditions are proposed. These results are not only of theoretical but also of practical value. Методом об‘єднання матрично-значних функціоналів Ляпунова і теореми порівняння досліджено зв‘язну стійкість за Ляпуновим і практичну стійкість великих систем з запізненням. Запропоновано ряд нових достатніх умов. Результати мають не лише теоретичний сенс, але також практичне значення.